2014
DOI: 10.1080/10495398.2014.933740
|View full text |Cite
|
Sign up to set email alerts
|

Influence of DGAT1 K232A Polymorphism on Milk Fat Percentage and Fatty Acid Profiles in Romanian Holstein Cattle

Abstract: Milk and dairy products are considered the main sources of saturated fatty acids, which are a valuable source of nutrients in the human diet. Fat composition can be adjusted through guided nutrition of dairy animals but also through selective breeding. Recently, a dinucleotide substitution located in the exon 8 of the gene coding for acyl CoA: diacylglycerol acyltransferase 1 (DGAT1), that alters the amino acid sequence from a lysine to an alanine (p.Lys232Ala) in the mature protein, was shown to have a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…The missense mutation K232A in DGAT1 showed to have significant effects on milk traits in cattle, which the A allele was associated with increased milk yield, whereas the K allele with increased fat and protein concentrations [8,9]. Moreover, the DGAT1 K232A was also contributed to influence the fatty acids contents of milk in both cattle and buffalo [10]. Polymorphisms of the DGAT1 were found to be fixed on allele K at K232A locus in some buffalo breeds, which were considered to be the primary responsibility for the high milk fat in buffalo [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The missense mutation K232A in DGAT1 showed to have significant effects on milk traits in cattle, which the A allele was associated with increased milk yield, whereas the K allele with increased fat and protein concentrations [8,9]. Moreover, the DGAT1 K232A was also contributed to influence the fatty acids contents of milk in both cattle and buffalo [10]. Polymorphisms of the DGAT1 were found to be fixed on allele K at K232A locus in some buffalo breeds, which were considered to be the primary responsibility for the high milk fat in buffalo [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of milk fatty acids depends on breed, lactation stage, environment, and animals' diet [10,27]. Moreover, fatty acid profile is affected by genetic factors, such as polymorphism of BLG, DGAT1, and Stearoyl-CoA Desaturase 1 (SCD1) genes [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that minisatellite markers in DGAT1 are associated with milk constituents in buffaloes (Cardoso et al, 2015). Tăbăran et al (2015) reported the influence of polymorphisms in DGAT1 on the percentage and profile of milk fat in Romanian Holstein cattle; therefore, they should be used in marker-assisted selection (Hill et al, 2016). Lacorte et al (2006) used polymerase chain reaction (PCR)-restriction fragment length polymorphism to reveal that SNPs in DGAT1 exhibited a high frequency of the A allele in Holstein and Gyr x Holstein F 1 cattle.…”
Section: Introductionmentioning
confidence: 99%